The Correlation Between Students’ Habit in Watching English Movies and Their Listening Skill at the Second Grade of SMAN 1 IV Koto - Hanifah Fajriati; Loli Safitri; Widya Syafitri; Reflinda Reflinda (Pusat Riset dan Inovasi Nasional, 2024)
This research was aimed to find and describe the correlation between students’ habit in watching English movie (variable x) and their listening skill (variable y). This research was conducted at the second grade of SMAN 1 IV Koto Agam Regency by the reason of there were still a lot of students who thought that listening is a difficult skill to learn and had low score in listening. This problem occurred because the students were still lack of exposure to the English to provide them with a comprehensible input in acquire the language especially listening skill. Moreover, theories said that watching English movies as a habit could be beneficial and could provide an input to develop students’ listening skill. However, there were not all of the students who had watching movie habit got good score in listening. Nevertheless, there were some of the students who had watching movie habit and got good score in listening. The method used in this research was quantitative method with the correlational design. The population of the research was all of the students from eleventh grade at SMAN 1 IV Koto and the sample was consisted of 33 students. The sample was taken by using random sampling technique. The instruments that were used in this research was questionnaire for measuring the students’ habit in watching English movie and listening comprehension test for measuring students’ listening skill. The researcher used Product Moment Correlation to see if there was any correlation between the two variables.The result showed that the value of correlation coefficient (rxy) was 0.223 which means that there was a positive low correlation between the variable x and variable y. Furthermore, the hypothesis testing showed that the index value rxy was lower than the index value of rt (0.223<0.355) which means that the H0 (null hypothesis) was accepted and Ha was rejected. Thus, there was unsignificant correlation between the variable x and variable y. However, this result may have been affected by internal threats. The students used of subtitle while watching movie was quite high which may prevent them to optimally receive the inputs and acquire the language especially listening skill.